2014
DOI: 10.4103/0973-1482.144587
|View full text |Cite
|
Sign up to set email alerts
|

Radiation induced bystander effect and DNA damage

Abstract: Bystander effects (BSEs) have been investigated for a long time but without much deliberation as to the cause in targeted cells and the subsequent effect in naïve cells. BSEs have traditionally been associated with radiation. Currently, this phenomenon is at a juncture where nuclear DNA damage is being debated as either essential or nonessential. If DNA damage is essential for the bystander signal (BSS) production then, this raises a number of questions about, radiotherapy and chemotherapy of cancer patients. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 99 publications
1
14
0
Order By: Relevance
“…It has been even hypothesized that senescence-inducing mechanisms can be applicable in the future as cancer therapies by arresting the proliferation of cancer cells through senescence induction [9][10][11]. However, radiobiological data from the last several years show that radiation is able to induce response in adjacent cells and tissues not directly subjected to radiation, the phenomenon termed the radiation induced bystander effect [reviewed in [12][13][14][15][16][17][18][19]. This effect may be mediated by soluble factors released by irradiated cells into the extracellular environment and/or by the passage of mediating molecules through intercellular gap-junction communication channels.…”
Section: Introductionmentioning
confidence: 99%
“…It has been even hypothesized that senescence-inducing mechanisms can be applicable in the future as cancer therapies by arresting the proliferation of cancer cells through senescence induction [9][10][11]. However, radiobiological data from the last several years show that radiation is able to induce response in adjacent cells and tissues not directly subjected to radiation, the phenomenon termed the radiation induced bystander effect [reviewed in [12][13][14][15][16][17][18][19]. This effect may be mediated by soluble factors released by irradiated cells into the extracellular environment and/or by the passage of mediating molecules through intercellular gap-junction communication channels.…”
Section: Introductionmentioning
confidence: 99%
“…Current study involves establishment of HCV infected Huh-7 cell line and evaluating the mRNA expression of glutathione reductase (GSR), COX-2, retinoblastoma protein (RB), poly (ADPribose) polymerase (PARP) and VEGF. P53 has been shown to play a pivotal role in DNA damage repair pathways, including double strand breaks (DSBs), single strand breaks, base excision and mismatch repairs (Jalal et al, 2014). We hypothesized that HCV causes the oxidative stress, which in turn leads towards DNA damage (detected by DNA damage and repair genes ATM, ATR, DNAPKCs, PARP) and influences the expression of genes involved in carcinogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…The unexposed cells have also been shown to display the radiological changes when placed with the exposed cell media by the intercellular communication and also through the factors released by the exposed cells into the media. [11] The major studies have revealed that gamma radiation at sublethal doses, inflicted damages to the cell membrane,[12] increases the lipid peroxidation and reduces the total antioxidant capacity. [13] These effects are caused by the free radicals generated by radiolysis of water within the cell.…”
Section: Discussionmentioning
confidence: 99%